PROGRAM BIMBINGAN DAN KONSELING BAGI SISWA TUNANETRA DI SEKOLAH INKLUSIF - Hilman Mangkuwibawa (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
One of the basic change in exceptional education is inclusive program. The most perspective population to have inclusive program are blind students. Potential development of blind students in inclusive program is not adequate with educational intervening class but guidance and counseling. This research aims to formulate guidance and Counseling program for blind students who are studying at YPI Senior High School Bandung through inclusive program. The result of this research produce guidance and counseling program which consist of (1) information service guidance (2) academic guidance and (3) social personal guidance.